Awareness Of Malaybalay City on Ordinance No. 962 On Plastic and Polystyrene: Basis for Intervention - Aliganga, Queences Kaye P; Arimas, Ayra Nove A (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Plastic pollution has become one of the world’s most critical environmental issues that people are facing today. In Malaybalay City, Article 7 Ordinance 962, known as Plastic and Polystyrene Regulation, was enacted to address the problem of banning single-use plastic. This study will assess the level of awareness of market vendors, other establishments vendors, and customers on Plastic and Polystyrene Regulation Article 7 Ordinance 962 in Malaybalay City. This research assessed the plastic and polystyrene regulation practices that are applied the most, and then the study formulated ordinance intervention for Malaybalay City. This study used a descriptive quantitative research design in data gathering. The instrument that used in gathering data for this study is a researcher-made questionnaire that utilizes a Likert scale and an open-ended questionnaire. Findings disclosed that the market vendors, other establishments vendors, and customers in Malaybalay City encounter problems in the awareness of plastic and polystyrene. The results overall mean was high awareness. The recommendation included bringing your bags and following the regulations, ordinances, and platforms such as signage and internet information to spread properly the said awareness of regulation. Based on the data gathered, mostly prefer a necessary resources and guidelines, continuous monitoring and evaluation that enables the market vendors, establishments vendors, and customers adopt and apply the regulation in the use of plastic bags, regulation in the use of polystyrene. Article 7 of ordinance No. 962, and adaptation of the residents on the mandate on “bring your own bag” program that must encourage individuals to strengthen the enforcement of regulation or law.